Planets and the Possibility of Life beyond Earth - Wiseman, Jennifer J. (Zygon, 2025)
The question of whether life exists beyond Earth has intrigued humans throughout history. Millennia of speculation have fueled both philosophy and theology, with contemplations of the spiritual state of alien beings shedding new light on that state of our own species. The relatively recent first scientific detections of planets outside our solar system, followed by a surge in further exoplanet discoveries and study, are reinvigorating these ancient questions of life beyond Earth. Although extraterrestrial life has not yet been found, astronomy and cosmology are revealing a universe intrinsically connected to life, as stars generate the chemical building blocks needed for planets to form and for life to thrive. This article summarizes new scientific advances in the discoveries of exoplanets, the search for life beyond Earth, and evolving habitability in the universe, setting the stage for fresh consideration by others of the rich theological implications.